THE DETERMINANTS OF PRODUCTION AND FEACIBILITY OF CHILI PEPPER IN PROVINCE OF SUMATERA UTARA - Rita Herawaty Bangun (Faculty of Animal and Agricultural Science, Diponegoro University, 2021)
Chili pepper is a horticultural commodity that has the potential to be cultivated in Sumatera Utara Province. It is a strategic commodity and has high economic value. This research aims to look at the factors that affect the production of chili pepper and analyze the feasibility of chili pepper farming. This research used cross-section data sourced from the Central Statistics Agency of Sumatera Utara Province. This research used multiple linear regression analysis and analysis of the return cost ratio (R / C. The results of the research showed that land area, productivity, and an average price of chili pepper gave an effect of 93.12 percent while 6.88 percent is influenced by other variables is based on the model. Based on simultaneous and partial harvesting test results, productivity and the average price of chili affect the production of chili pepper, based on the analysis of revenue cost ratio (R / C), chili pepper farming is feasible to be cultivated because it is economically profitable.